Kopi Toleransi: Is a Silent Path Finding The Divining Light - Purjatian Azhar; Bante Dhirapuno; Mln. Muhammad Idris; RP. Emanuel Sonny Wibisono (KOLABORASI: Journal of Multidisciplinary, 2026)
This article will explain the Kopi Toleransi movement in Medan City in creating, caring for, and fostering tolerance among religious communities. This movement is represented by young religious figures from Nahdlatul Ulama (NU), Ahmadiyah, Buddhism, Catholics and Protestants. The Kopi Toleransi Movement itself was founded in 2017 and until now it has produced many real works in religious social life in the city of Medan. Kopi Toleransi moves from the grassroots by educating the public on how to live tolerantly with people of different religions. As for the activities that have been carried out over the past three years, namely the social service to clean houses of worship which is done together, the social service for blood donation which is routinely carried out together regardless of religion. the result over the past three years the Kopi Toleransi movement can be accepted by the people of Medan city. The suspicion that became a great wall has now begun to crumble with the presence of a copy of tolerance which is clear evidence that the coffee Kopi Toleransi erance movement is not only gathering religious leaders but also real action.